Reine Rechtslehre Einleitung in die rechtswissenschaftliche Problematik (Studienausgabe der 1. Auflage 1934) - Kelsen, Hans (Mohr Siebeck, 2020)
Hans Kelsen's »Pure Theory of Law«, which was published in 1934, is one of the key works on legal theory in the 20th century. In it, Kelsen presents a theory in which he separates the law from morality on the one hand and on the other hand from proven fact, a theory which was also critical of ideologies. Anyone wanting to think about the structure and the validity of the law and the characteristics of jurisprudence, in short, anyone wanting to think about the normativity of the law, will inevitably have to deal with the »Pure Theory of Law.« The first edition of this work, which has been translated into approximately a dozen languages, was reprinted several times in German, but is currently out of print. It is now available as a student edition, which is intended to encourage those interested in the law to read through it and to give it their careful and critical consideration.